MicroRNA biogenesis, functionality and cancer relevance - Kusenda, Branislav; Mraz, Marek; Mayer, Jiri; Pospisilova, Sarka (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2006)
BACKGROUND: MicroRNAs (miRNA) are small non-coding RNAs that negatively regulate gene expression in a sequence- specific manner. Post-transcriptional silencing of target genes by miRNA occurs either by specific cleavage of homologous mRNA or by specific inhibition of protein synthesis. MiRNAs are essential regulators of various processes such as proliferation, differentiation, development, cell death and interaction between virus and host cell. AIM: The aim of this paper is to summarize the main findings from research on miRNA biogenesis, functionality and cancer relevance. METHOD: A narrative literature review of all of the relevant papers known to the authors was conducted. RESULTS: Several human diseases including cancer are associated with aberrant regulation of miRNAs expression or deficiency in miRNA biogenesis. Analysis of miRNA expression signatures can serve as a valuable tool for cancer classification, diagnostics and prediction of tumor behavior. CONCLUSIONS: There has been demonstrated a possibility to use these microRNA signatures for a specific cancer classification with potential predictive and therapeutic value. The known data provide evidence that microRNAs may open new ways for cancer diagnosis, prognosis estimation and therapy.
Keywords: mikro RNA; viry; Neoplasms; exprese genu; Gene Expression; zvířata; Humans; nádory; Viruses; MicroRNAs; lidé; Animals